Contrast-enhanced ultrasound in the evaluation of parotid gland lesions: an update of the literature. (May 2016) - David, E; Cantisani, V; De Vincentiis, M; Sidhu, PS; Greco, A; Tombolini, M; Drudi, FM; Messineo, D; Gigli, S; Rubini, A; Fresilli, D; Ferrari, D; et al.
High-resolution ultrasound is the first line examination for parotid gland diffuse disease and focal lesions, normally using grey-scale and colour-Doppler ultrasound. Unfortunately, grey-scale and colour-Doppler ultrasound features of benign and malignant salivary gland lesions may overlap, particularly with benign tumors, where pleomorphic adenomas are often indistinguishable from malignant lesions. With atypical lesions, contrast-enhanced magnetic resonance imaging is usually the second level imaging modality requested. The introduction of ultrasound contrast agents has opened further possible perspectives to improve the interpretation of parotid diseases, particularly the differentiation between benign and malignant lesions. We present a review of the current literature on contrast-enhanced ultrasound for the assessment of parotid gland lesions, considering all characteristics of the technique, evidence of usefulness, future perspectives and limitations.